2018
DOI: 10.1039/c7ra11740j
|View full text |Cite
|
Sign up to set email alerts
|

Activated carbons modified by magnesium oxide as highly efficient sorbents for acetone

Abstract: Porous activated carbon modified with MgO was synthesized by an evaporation-induced self-assembly (EISA) method for its application to acetone capture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 58 publications
2
12
0
Order By: Relevance
“…The nitric acid modified AC exhibited high adsorption capacity of 433.9 mg g -1 on acetone, which might be attributed to the interaction between carboxylic groups and acetone. Similarly, Zhou et al (2018) observed magnesium oxide modified AC also presented high equilibrium amount of acetone (432.7 mg g -1 ) at 25℃, 85.21 g m -3 . It indicated that introduced oxygen functional groups offered active sites, which had strong adsorption affinity on polar acetone.…”
Section: Activated Carbonsupporting
confidence: 58%
“…The nitric acid modified AC exhibited high adsorption capacity of 433.9 mg g -1 on acetone, which might be attributed to the interaction between carboxylic groups and acetone. Similarly, Zhou et al (2018) observed magnesium oxide modified AC also presented high equilibrium amount of acetone (432.7 mg g -1 ) at 25℃, 85.21 g m -3 . It indicated that introduced oxygen functional groups offered active sites, which had strong adsorption affinity on polar acetone.…”
Section: Activated Carbonsupporting
confidence: 58%
“…To the best of our knowledge, activated carbons have never been used for the Guerbet reaction whereas MgO dispersed on activated carbons has been proposed as sorbent for different gaseous species, such as CO 2 [19], H 2 S [20,21], and organics [22,23] strongly increasing the adsorption capacity of the raw activated carbon.…”
Section: Introductionmentioning
confidence: 99%
“…30 Zhou et al modied AC by MgO and found that increasing of MgO content could greatly enhance the chemical property but suppress the physical property. 31 Great efforts have been made to correlate physico-chemical properties and adsorption capacities of VOCs such as toluene, xylene and alkyl halides. [32][33][34] Other than aforementioned VOCs, acetone is a typical strong polar VOC, which may exhibit different adsorption property to nonpolar or weak polar ones.…”
Section: Introductionmentioning
confidence: 99%